Impact of absorptive capacity and ambidexterity on innovation - Del Carpio Gallegos, Javier Fernando; Miralles, Francesc; Soria Gomez, Eduardo Javier (Universidad Autónoma del Caribe, 2021)
This study attempts to design an approach showing how absorptive capacity and ambidexterity are related to technological innovation in Peruvian manufacturing firms. A structural equation model is proposed. The sample is made up of 783 manufacturing firms. It was found that although Peruvian manufacturing firms invest little money in research and development, they are capable of developing dynamic capabilities, such as absorptive capacity and ambidexterity in order to better carry out technological innovation.

Este estudio intenta diseñar un enfoque que muestre cómo la capacidad de absorción y la ambidiestralidad se relacionan con la innovación tecnológica en las empresas manufactureras peruanas. Se propone un modelo de ecuación estructural. La muestra está compuesta por 783 empresas manufactureras. Se encontró que, aunque las empresas manufactureras peruanas invierten poco en investigación y desarrollo, son capaces de desarrollar capacidades dinámicas, como capacidad de absorción y ambidiestralidad, para llevar a cabo mejor la innovación tecnológica.
Keywords: Absorptive capacity; Ambidexterity; Capacidad de absorción; Technological innovation; Ambidiestralidad; Innovación tecnológica; Manufacturing; Manufactura; https://purl.org/pe-repo/ocde/ford#5.02.04